Marfan syndrome: pathologic features of aneurysm with dissection and aortic dissection - R. K. Zhuraev; P. V. Kuzyk (Patologìâ)
The article presents the pathologic changes in the aortic wall in patients with MFS (three men at the age of 25, 27, 35 years) operated on the aneurysm with dissection of the ascending aorta. Morphological changes in the middle of the shell of the aorta in patients with MFS were characterized by severe restructuring with profound irreversible alterative changes in all of its components. The pathological process captured media of the aorta throughout its entire length, not just in the areas of rupture and separation. The main pathomorphological signs of MFS were the focal accumulation of mucoid substances, ribbon-like nuclear-free zones, degenerative changes in smooth muscle cells, the formation of cystic media degeneration cavities, changes in elastic fibers - fragmentation, hyperelastosis, multiplication, thinning and straightening, areas of significant elastolysis. Multiple CMD was detected in all patients with MFS, the changes revealed the same type, but at different stages of the process.